The labial–coronal effect revisited: Japanese adults say pata, but hear tapa - Tsuji, Sho; Gomez, Nayeli Gonzalez; Medina, Victoria; Nazzi, Thierry; Mazuka, Reiko (Cognition, 2012)
► Japanese has a labial–coronal bias overall, but a coronal–labial bias for plosives. ► Japanese participants have a labial–coronal bias in production of plosive sequences. ► Japanese participants have a coronal–labial bias in perception of plosive sequences. ► Production bias is articulatory motivated and possibly language-general. ► Perception bias is influenced by language-specific distributions. The labial–coronal effect has originally been described as a bias to initiate a word with a labial consonant–vowel–coronal consonant (LC) sequence. This bias has been explained with constraints on the human speech production system, and its perceptual correlates have motivated the suggestion of a perception–production link. However, previous studies exclusively considered languages in which LC sequences are globally more frequent than their counterpart. The current study examined the LC bias in speakers of Japanese, a language that has been claimed to possess more CL than LC sequences. We first conducted an analysis of Japanese corpora that qualified this claim, and identified a subgroup of consonants (plosives) exhibiting a CL bias. Second, focusing on this subgroup of consonants, we found diverging results for production and perception such that Japanese speakers exhibited an articulatory LC bias, but a perceptual CL bias. The CL perceptual bias, however, was modulated by language of presentation, and was only present for stimuli recorded by a Japanese, but not a French, speaker. A further experiment with native speakers of French showed the opposite effect, with an LC bias for French stimuli only. Overall, we find support for a universal, articulatory motivated LC bias in production, supporting a motor explanation of the LC effect, while perceptual biases are influenced by distributional frequencies of the native language.